The Growth and Yield of IPB 3S Rice Variety With NPK and Rice Straw Compost - Sataral, Mihwan; Nangge, Marlinda; Yatim, Herwin (Jurnal Online Pertanian Tropik, 2020)
To minimize the use of inorganic fertilizers is by giving rice straw compost to the soil. The rice straw compost is a potential organic material for lowland rice plants. This study was aimed to determine the effect of the combination of NPK fertilizer and rice straw compost on the growth and yield of IPB 3S rice variety. This research was carried out on farmers' land in Dowiwi village, Simpang Raya sub-district, Banggai district. The study used a factorial randomized block design with two factors. Factor A (NPK) consisting of four levels namely A1 (62.5 kg / ha), A2 (125 kg / ha), A3 (187.5 kg / ha) and A4 ( 250 kg / ha). Factor B of rice straw compost (B) consisting of four levels, namely B1 (1.25 tons / ha), B2 (2.5 tons / ha), B3 (3.75 tons / ha), and B4 (5 tons / Ha). The results showed that rice straw compost can be increased plant height and 1000 grains weight. The interaction of NPK and rice straw compost (NPK 62.5 kg/ha + 5 tons/ha) was able to minimize the use of NPK fertilizer by 75% in panicle length and 1000 grains weight. REFERENCES Amrah ML. (2008). Pengaruh manajemen jerami terhadap pertumbuhan dan hasil padi sawah (Oryza sativa L.). Skripsi. Bogor: Institut Pertanian Bogor. Arafah, Sirappa MP. (2013). Kajian penggunaan jerami dan pupuk N, P, dan K pada lahan sawah irigasi. Jurnal Ilmu Tanah dan Lingkungan. 4(1): 15-24 Barus Y. (2012). Application of rice straw compost with different bio activators on the Growth and yield of the rice plants. Journal of Tropical Soils. 17(1): 25-29. Doi: 10.5400/jts.2011.17.1.25 Boroomand N, Grouh MSH. (2012). Macroelements nutrition (NPK) of medicinal plants. Journal of Medicinal Plants Research 6(12): 2249-2255 Diptaningsari D. (2013). Analisis keragaman karakter agronomis dan stabilitas galur harapan padi gogo turunan padi lokal Pulau Buru hasil kutur antera. Disertasi. Bogor: Institut Pertanian Bogor. Hartatik W, Setyorini D. (2008). Validasi rekomendasi pemupukan NPK dan pupuk organik pada padi sawah. hlm 275-283 Dalam : M. Anda, B. Hendro, Irawan, E. Surmaini, Wahyunto, dan E. Husen (eds). Prosiding Seminar Nasional Dialog Sumberdaya Lahan Pertanian. Bogor: Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian. Hartatik W, Widowati LR. (2015). Pengaruh Pupuk Majemuk NPKS dan NPK terhadap Pertumbuhandan Hasil Padi Sawah pada Inceptisol. Jurnal Penelitian Pertanian Tanaman Pangan. 34(3):175-186. Hosseini SM, Aziz HA. (2013). Evaluation of thermochemical pretreatment and continuous thermophilic condition in rice straw composting process enhancement. Bioresource Technology. 133: 240“247. doi: 10.1016/j.biortech.2013.01.098 Idawati, Rosnina, Jabal, Sapareng S, Yasmin, Yasin SM. (2017). Penilaian kualitas kompos jerami padi dan peranan biodekomposer dalam pengomposan. Journal TABARO. 1(2): 127-135 Juwita Y. (2014). Teknologi Pengolahan, Manfaat, dan Kendala Penggunaan Kompos Jerami Padi.. hlm 769-775. Dalam: S. Herlinda, Suwandi, F.H. Taqwa, Tanbiyaskur, Eko Handayanto, Sarjan, N. Aini, Rajiman, dan Mardhiana (eds). Prosiding Seminar Nasional Lahan Suboptimal. Palembang: Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) UNSRI. Kaya E, (2013). Pengaruh kompos jerami dan pupuk NPK terhadap N-tersedia tanah, serapan-N, pertumbuhan dan hasil padi sawah (Oryza sativa L.). Prosiding FMIPA Universitas Pattimura. Ambon, Hal. 41-47 Ma’sum FQA, Kurniasih B, Ambarwati E. (2016). Pertumbuhan dan hasil padi sawah (Oryza sativa L.) pada beberapa takaran kompos jerami dan zeolite. Jurnal Vegetalika. 5(3): 29-40 Noviani PI, Slamet S, Citraresmini A. (2018). Kontribusi kompos jerami-Biochar dalam peningkatan P-tersedia, jumlah populasi BPF dan hasil padi sawah. Jurnal Ilmiah Aplikasi Isotop dan Radiasi. 14(1): 47-57 Pranata M, Kurniasih B. (2019). Pengaruh pemberian pupuk kompos jerami padi terhadap pertumbuhan dan hasil padi (Oryza sativa L.) pada kondisi salin. Jurnal Vegetalika. 8(2): 95-107. Sabran I, Soge YP, Wahyudi HI. (2015). Pengaruh pupuk kandang ayam bervariasi dosis terhadap pertumbuhan dan hasil tanaman kacang tanah (Arachis hypogeae L.) pada entisol Sidera. Jurnal Agrotekbis. 3(3) : 297-302 Sitepu RB, Anas I, Djuniwati S. (2017). Pemanfaatan jerami sebagai pupuk organik untuk meningkatkan pertumbuhan dan produksi padi (Oryza sativa). Buletin Tanah dan Lahan, 1(1): 100-108 Surahman M, Budiman C, Aswidinnoor H, Qadir A, Diaguna R. (2017). Optimization of NPK and silica fertilization for seed production of IPB 3S rice varieties in Pinrang, South Sulawesi. International Journal of Agronomy and Agricultural Research. 11(6): 102-107 Susanto U, Daradjat AA, Suprihatno B. (2003). Perkembangan pemuliaan padi sawah di Indonesia. Jurnal Litbang Pertanian 22(3) : 125-131